2015
DOI: 10.1590/s1980-65742015000300007
|View full text |Cite
|
Sign up to set email alerts
|

Stretch breaks in the work setting improve flexibility and grip strength and reduce musculoskeletal complaints

Abstract: Abstract--This study investigated the effect of a stretch break program (SBP) on the flexibility, strength and musculoskeletal complaints of storage (SW) and administrative (AW) sector workers. Twenty-six male workers were randomly selected: 16 workers from the storage sector and ten workers from the administrative sector. We applied the Physical Activity Questionnaire and Musculoskeletal Questionnaire and evaluated flexibility and grip strength before and after 6 months of the SBP. The SPB decreased the SW gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…This finding is consistent with the literature that points to the lack of safety at work and unfavourable ergonomic conditions in this environment, and the NTEP analysis shows association with many groups of ICD-10, as well as indicates a serious risk (grade 3), regardless of the type of activity in civil construction 7 . The knowledge on this relationship shows possibilities of action of Physical Therapy, since studies show that workplace exercises and ergonomic analysis applied to work have an impact on the quality of health of workers 20 . In relation to retirees, it was not possible to access information about the former profession and the associations observed in this study indicated the effect of the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the literature that points to the lack of safety at work and unfavourable ergonomic conditions in this environment, and the NTEP analysis shows association with many groups of ICD-10, as well as indicates a serious risk (grade 3), regardless of the type of activity in civil construction 7 . The knowledge on this relationship shows possibilities of action of Physical Therapy, since studies show that workplace exercises and ergonomic analysis applied to work have an impact on the quality of health of workers 20 . In relation to retirees, it was not possible to access information about the former profession and the associations observed in this study indicated the effect of the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…In the articles about physical abilities, we observe the studies of Machado-Matos et al 8 and Martins et al 9 cited above. About that capacities, Grande et al 10 in your study with thepurpose to investigate the effectiveness of workplace exercise for employee health by means of health-related physical activity components and verified the variables in the study not changed with intervention.…”
Section: Discussionmentioning
confidence: 78%
“…In the study of Machado-Matos et al 8 with the to evaluate the impact of a workplace exercise program on neck and shoulder pain and flexibility in office workers observed improvements in pain reduction and increased flexibility. And the study of Martins, Zicolau et al 9 that investigated the effect of a stretch break program (labor gymnastics program) on the flexibility, strength and musculoskeletal complaints of storage and administrative sector workers and verified that program was able contribute to improve flexibility and musculoskeletal complaints in the regions that are affected by higher rates of work-related injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants in studies on WPA were engaged in administrative functions in either the public 15,[19][20][21]23,24,26,27,29,32,39,46,55 or the private sector 7,18,38,40,41,44,45,47,50,52,53 . The remainder of the samples included employees working in industrial production 6,18,34,36,41,42,48,52 , civil construction 17 , storage 18,36,50 , general services 27,32,33 , call centers 28,43 , as urban public transport drivers 51 , and also university students 52 . The latter was an experimental study, for this reason the participants were not workers as in the other studies.…”
Section: Participants' Occupation/functionmentioning
confidence: 99%